Metabolic dysfunction-associated fatty liver disease: current therapeutic strategies - Al Hashmi, Khamis; Giglio, Rosaria Vincenza; Pantea Stoian, Anca; Patti, Angelo Maria; Al Waili, Khalid; Al Rasadi, Khalid; Ciaccio, Marcello; Rizzo, Manfredi (Frontiers in Nutrition, 2024)
The definition of “Metabolic Associated Fatty Liver Disease – MAFLD” has replaced the previous definition of Nonalcoholic Fatty Liver Disease (NAFLD), because cardiometabolic criteria have been added for the prevention of cardiological risk in these patients. This definition leads to an in-depth study of the bidirectional relationships between hepatic steatosis, Type 2 Diabetes Mellitus (T2DM), Cardiovascular Disease (CVD) and/or their complications. Lifestyle modification, which includes correct nutrition combined with regular physical activity, represents the therapeutic cornerstone of MAFLD. When therapy is required, there is not clear accord on how to proceed in an optimal way with nutraceutical or pharmacological therapy. Numerous studies have attempted to identify nutraceuticals with a significant benefit on metabolic alterations and which contribute to the improvement of hepatic steatosis. Several evidences are supporting the use of silymarin, berberine, curcumin, Nigella sativa, Ascophyllum nodosum, and Fucus vesiculosus, vitamin E, coenzyme Q10 and Omega-3. However, more evidence regarding the long-term efficacy and safety of these compounds are required. There is numerous evidence that highlights the use of therapies such as incretins or the use of Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) inhibitors or other similar therapies which, by assisting existing therapies for pathologies such as diabetes, hypertension, insulin resistance, have given a breakthrough in prevention and the reduction of cardiometabolic risk. This review gave an overview of the current therapeutic strategies that are expected to aid in the treatment and prevention of MAFLD.